SINTESIS NANOPARTIKEL ZnO DIDOPING Sn DENGAN METODE KOPRESIPITASI - Rini Anggraini Pakpahan; Sri Utami Kholila Mora Siregar; Jainal Abidin; Julianto Lubis (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
In this research, synthesize of ZnO doped Sn nanoparticles was done by coprecipitation method. The raw material are the powder of zinc acetate dihydrate, the powder of tin (II) chloride dihydrate, HCl solution, and ammonium chloride solution. The doping of Sn powder used in concentration 0 %wt, 1 %wt, 2 %wt, 3 %wt, 4 %wt, and 5%wt. This research was done to know the effect of doping Sn toward ZnO nanoparticles structure. Structure and phase composition of ZnO doped Sn was known by XRD characterization, then Scanning Electron Microscopy (SEM) to know the morphology of ZnO nanoparticles doped Sn. The XRD patterns indicated that ZnO doped Sn nanoparticles crystallize in hexagonal Zincite structure. The crystallite size was analyzed by using Material Analysis Using Diffraction (MAUD) software and found to be in the range of 22-97 nm. The result of SEM test showed that the morphological surface of the nanoparticles was affected by Sn doping.